Hydrodynamic improvement by adding inlet baffles on centrifugal pump for reducing cavitation instabilities. (January 2023) - Wei, Zhicong; Tao, Ran; Xiao, Ruofu; Hu, Honglin
Cavitation instability is a common phenomenon that causes vibration and noise of turbomachinery. In this study, an attempt is made to suppress the cavitation instability. A high-speed centrifugal pump with inducer is taken as the research objective. Four baffles are evenly arranged at the inlet of the inducer as a hydrodynamic improvement. The energy characteristics of the pump are measured on a closed hydraulic test rig. The pressure, vibration, and noise under different flow rates and different cavitation number are acquired for comparative analyses. Experimental results show that the energy characteristics changed after hydrodynamic improvement. The original pump is mainly affected by y- direction vibration and is clearly suppressed in the new pump. The low-frequency pressure pulsation under partial flow rate condition can be effectively suppressed. The baffles can also reduce the broadband center frequency at the pump outlet and change the relationship between center frequency and cavitation number. These results show that the hydrodynamic improvement at the inlet helps the suppression of cavitation instability of the high-speed centrifugal pump.